Prospective teachers' design of STEAM learning units: STEAM capabilities' analysis - Ahlam Anabousy; Wajeeh Daher (OmniaScience, 2022)
STEM education is a new field within which understandings of what constitutes effective practice, and how this can be supported, are still in their infancy. The present research describes the experiences of prospective elementary school teachers in designing collaboratively STEM activities. This designing experiences occurred in a context of a PD program called "Introduction to STEM education". During the STEM PD program, the pre-service teachers worked in six groups. Each group included three pre-service teachers who worked together throughout the PD program. Three written STEM units of three groups were chosen to be analyzed. In analyzing the STEM units, we referred to the STEM capabilities which consists of three components: STEM knowledge, skills and ways of thinking. The findings show different possibilities that STEM education can afford for task design. In terms of the integration of disciplines, the three analyzed units included activities in which, mostly, at least two disciplines were dominant. In terms of STEM skills, the designed unites targeted mainly the individual learning STEM skill instead of collaborative skills, which emphasize the need to pay special emphasis to this issue. Finally, in terms of STEM ways of thinking, analytical and evidence-based ways of thinking prevailed in the three units. The previous findings point at the importance of support for pre-service teachers to design STEM activities for implementation in their classrooms.